Thank you for the opportunity to help you with your question!
=3x^2*-4x +3x^2*-5+2 * -4x + 2* -5
= - 12x^3 - 15x^2 - 8x -10....................................answer
Could you explain that one?
open the brackets and multiply each term with other
now multiply the numbers in each term and add the exponents of variables
= -12 x^(2+1) - 15 x^2 - 8x -10
= - 12x^3 - 15x^2 - 8x -10
please message the step in which you have doubt if any
There is one the -12x^2+1.. is that part of the exponent?
= -12x^(2+1) you can see that there are x^2 and x so when we multiply that it becomes x^(2+1) = x^3
and the others are numbers 3 and -4 ,so 3*-4 = -12,
so together it is -12x^3
you got it?
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?